2009
DOI: 10.1186/1824-7288-35-39
|View full text |Cite
|
Sign up to set email alerts
|

Regurgitation in healthy and non healthy infants

Abstract: Uncomplicate regurgitation in otherwise healthy infants is not a disease. It consists of milk flow from mouth during or after feeding. Common causes include overfeeding, air swallowed during feeding, crying or coughing; physical exam is normal and weight gain is adequate. History and physical exam are diagnostic, and conservative therapy is recommended. Pathologic gastroesophageal reflux or gastroesophageal reflux disease refers to infants with regurgitation and vomiting associated with poor weight gain, respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 111 publications
(117 reference statements)
1
8
0
Order By: Relevance
“…Indrio et al reported GERD refers to infants with regurgitation and vomiting associated with poor weight gain. 8 These results were similar to the study of De et al, where 47% of children with IGERQ score >5 had inadequate weight gain. Orenstein study showed 26% of children with GERD had inadequate weight gain.…”
Section: Discussionsupporting
confidence: 90%
“…Indrio et al reported GERD refers to infants with regurgitation and vomiting associated with poor weight gain. 8 These results were similar to the study of De et al, where 47% of children with IGERQ score >5 had inadequate weight gain. Orenstein study showed 26% of children with GERD had inadequate weight gain.…”
Section: Discussionsupporting
confidence: 90%
“…Currently, several known therapies use histamine H2 receptor antagonist to cure peptic ulcers (even relapses) and affect gastric acid secretion [46] . Treatments based on the HRH2 antagonist are also commonly used in gastro-esophageal reflux diseases in infants and children [47] , [48] . Among the putative plant miRNAs targets, one protein is also important for the therapeutics - nectin-4, alternatively referred to as poliovirus receptor-related protein 4 (PVRL4).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the other underlying conditions may be ruled out with a detailed history or laboratory evaluation. Overfeeding due to excessive feeding volumes is elicited by history and observation, whereas sepsis and pyelonephritis may present with poor clinical condition and a positive acute phase reactant (i.e., WBC, CRP and Interleukin‐6) (Hofer, Zacharias, Muller, & Resch, ; Indrio, Riezzo, Raimondi, Cavallo, & Francavilla, ). Obstruction in the gastrointestinal system manifests in the abdominal radiograph, whereas endocrine derangements and inborn errors of metabolism show abnormalities in the electrolyte panel, again with a poor clinical condition (Hryhorczuk & Lee, ; Nimkarn, Lin‐Su, & New, ; Piazza & Stoll, ).…”
Section: Discussionmentioning
confidence: 99%